Greek-Turkish Relationship and NATO. - Moustakis, Fotios (Taylor & Francis, 2003)
This publication shows that the Eastern Mediterranean, having been transformed from a region of secondary importance during the Cold War to one of greater importance for the western interests in the post-Cold War era, is in a state of flux.